Devaluation Expectations and the Stock Market The Case of Mexico in 1994/1995 - Becker, Törbjörn I. (International Monetary Fund, 2000)
Using company-level data, this paper examines the relative stock-market performance of firms with different foreign-exchange exposures around the time of the 1994/95 Mexican crisis. Contrary to what one might have expected given the alleged peso overvaluation, exporting firms outperformed the market beginning in late 1993. Although interest rates fail to show a clear confidence loss in the exchange rate regime, the relative performance of net exporters suggests that expectations of devaluation increased continuously. The methodology presented is relevant beyond the Mexican case: sectoral differences in stock market performance may constitute valuable leading indicators of exchange rate changes in emerging markets